2018
DOI: 10.21767/2572-5610.10045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infection among School Children in Taif

Abstract: Descriptive cross section study among Taif primary school randomize samples were chosen age range is from 4-14 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
1
5
4
Order By: Relevance
“…It agrees with the reports from Pahang, Malaysia (18.5%) [ 69 ]; the Philippines (12.1%) [ 76 ]; and Karnataka, India (9%) [ 82 ]. However, the result of this study was higher than that of studies in Saudi Arabia (2%) [ 54 ], Iran (0.6%) [ 59 ], Thailand (0.73%) [ 61 ], Ghana (0.21%) [ 63 ], Cameroon (7.3%) [ 68 ], and Mexico (5%) [ 70 ]. In contrast, the results of the present study were lower than those of studies from Côte d'Ivoire (56%) [ 52 ]; Tanzania (28.5%) [ 53 ]; Sudan (31.2%) [ 64 ]; Kenya (23.9%) [ 65 ]; Kut city, Iraq (41%) [ 66 ]; Iraq (88%) [ 67 ]; Burkina Faso (66.5%) [ 72 ]; and Libya (21.14%) [ 78 ].…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…It agrees with the reports from Pahang, Malaysia (18.5%) [ 69 ]; the Philippines (12.1%) [ 76 ]; and Karnataka, India (9%) [ 82 ]. However, the result of this study was higher than that of studies in Saudi Arabia (2%) [ 54 ], Iran (0.6%) [ 59 ], Thailand (0.73%) [ 61 ], Ghana (0.21%) [ 63 ], Cameroon (7.3%) [ 68 ], and Mexico (5%) [ 70 ]. In contrast, the results of the present study were lower than those of studies from Côte d'Ivoire (56%) [ 52 ]; Tanzania (28.5%) [ 53 ]; Sudan (31.2%) [ 64 ]; Kenya (23.9%) [ 65 ]; Kut city, Iraq (41%) [ 66 ]; Iraq (88%) [ 67 ]; Burkina Faso (66.5%) [ 72 ]; and Libya (21.14%) [ 78 ].…”
Section: Discussioncontrasting
confidence: 79%
“…The pooled prevalence of Cryptosporidium species was 5.93%, which is higher than other studies from Saudi Arabia (3%) [ 54 ], Bulgaria (1.69%) [ 56 ], Spain (1%) [ 57 ], Iran (0.4%) [ 59 ], Senegal (0.3%) [ 60 ], Dhaka (0.5%) [ 75 ], Libya (0.8%) [ 78 ], and China (2.4%) [ 83 ]. The result of this meta-analysis was lower than that of studies conducted in Iraq (10.4%) [ 14 ], Ghana (8.5%) [ 63 ], Kenya (13%) [ 65 ], Iraq (12.5%) [ 66 ], Cameroon (44%) [ 68 ], and the Philippines (22%) [ 76 ].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Similar studies by Liao et al [ 60 ], Reh et al [ 61 ], Harizanov et al [ 62 ], and Staudacher et al [ 63 ], who reported a prevalence of 28.6%, 28%, 25.53%, and 25.4% in the Democratic Republic of Congo, Spain, Bulgaria and Rwanda, respectively, were in close agreement with the current finding. However, the findings of this study was higher than those of studies conducted by Ismail, [ 64 ], 18.7% in Saudi Arabia, Coulibaly et al [ 65 ], 18.7% in Côte d'Ivoire, Venkatajothi, [ 66 ], 17.4% in Tanzania and Abu-Madi et al [ 67 ], 5.93% in Qatar. On the other hand, this result was lower than the reports by Sylla et al [ 68 ], 32.6% in Senegal, Sanprasert et al [ 69 ], 37.8% in Thailand, Al-Jawabreh et al [ 70 ], 39.21% in Palestine, Tigabu et al [ 71 ], 39.84% in Ethiopia, Walana et al [ 72 ], 42.9% in Ghana, Suliman et al [ 73 ], 54.2% in Sudan, Karshima, [ 74 ], 54.8% in Nigeria, Kimosop et al [ 75 ], 56% in Kenya, Pasaribu et al [ 76 ], 57.4% in Indonesia, Quihui et al [ 77 ], 65% in Mexico, Yusuf et al [ 78 ], 72.3% in Malaysia, Nsagha et al [ 79 ], 74.3% in Cameroon, Erismann et al [ 80 ], 84.7% in Burkina Faso, Osman et al [ 81 ], 85% in Libya, and hamady obeid Al-Taei, [ 82 ], 98.8% in Iraq.…”
Section: Discussioncontrasting
confidence: 80%